Development of a Clinical Risk Assessment Score for Respiratory Distress Due to Respiratory Infections in Early Infancy - Cristina Elena Singer; Cristina Popescu; Diana-Maria Trasca; Renata-Maria Varut; Rebecca-Cristiana Serban; Jaqueline Abdul-Razzak; Virginia-Maria Radulescu (Children)
Background/Objectives: Neonatal and infant respiratory distress carries high morbidity, and severity can vary with gestational maturity and perinatal factors. Early risk stratification may improve outcomes, but existing assessment tools do not fully address age-related risk differences. We aimed to develop and validate a Neonatal Clinical Risk Assessment Score (N-CRAS) for predicting severity in neonates and young infants with respiratory distress due to respiratory infection. Methods: This pilot score was applied exclusively to a cohort of forty neonates and young infants with respiratory distress secondary to infectious causes, as defined by clinical and laboratory parameters. Clinical variables (gestational age, delivery mode, birth weight category, and APGAR score) were recorded and analyzed for associations with illness severity. We developed the N-CRAS (0–5 points) encompassing five indicators of severe illness (respiratory infection, metabolic disorder, need for symptomatic treatment, mechanical ventilation, and intubation), each contributing 1 point. Patients were stratified as low (0–1), moderate (2–3), or high (4–5) risk. Chi-square tests and Spearman correlation assessed associations, and an ROC curve evaluated the score’s predictive performance for intubation. Results: No individual perinatal factor was significantly associated with respiratory illness severity. The N-CRAS increased with infant age (p < 0.05), indicating older infants tended to have more severe disease. All study infants who required intubation fell into the high-risk category (score ≥ 4). The N-CRAS demonstrated excellent discrimination for predicting intubation (ROC area under the curve = 1.00). Conclusions: In this pilot study, the N-CRAS demonstrated a strong correlation with clinical severity and successfully identified all infants who required intubation. However, given the small cohort size and limited number of severe cases, these findings should be interpreted cautiously. Further external validation in larger and more diverse neonatal populations is essential to confirm its predictive utility.